Use of Beauveria bassiana in combination with commercial insecticides to manage Phauda flammans (Walker) (Lepidoptera: Phaudidae): Testing for compatibility and synergy - Chen, Xue-Min; Wang, Xiao-Yun; Lu, Wen; Zheng, Xia-Lin (Journal of Asia-Pacific entomology, 2021)
[Display omitted] •A new strain of Beauveria bassiana was identified from Phauda flammans larvae.•B. bassiana PfBb can effectively control P. flammans larvae.•Beta cypermethrin is the most compatible with B. bassiana PfBb.•B. bassiana PfBb mixed with beta cypermethrin had a synergistic effect. An entomopathogenic fungal strain, Beauveria bassiana PfBb, was identified from Phauda flammans (Lepidoptera: Phaudidae) larvae. The compatibility and synergy of B. bassiana PfBb employed in combination with three concentrations (i.e., recommended concentration, 20% and 10% of the recommended concentration) of five commercial insecticides were determined. Beta cypermethrin at 10% of recommended concentration had the lowest inhibitory effect on the mycelial growth of B. bassiana PfBb compared with other insecticides. Insecticides utilized at recommended concentration had no significant effect on the sporulation of B. bassiana PfBb, while the extent of their effect at 20% and 10% of recommended concentration differed among insecticides. Insecticides at 10% of recommended concentration had the lowest inhibition of sporulation and conidial germination compared with other concentrations. The conidial germination of B. bassiana PfBb was the highest after treatment with beta cypermethrin at 10% of recommended concentration. The cumulative mortality for 1 × 107 spores/mL B. bassiana PfBb combined with each insecticide at 10% of recommended concentration was higher than that observed with the application of insecticides alone. The percent cadavers of Phauda flammans larvae observed after treatment with B. bassiana PfBb combined with beta cypermethrin at 10% of recommended concentration were not significantly different from those observed after infection with B. bassiana PfBb alone. Our findings demonstrate that B. bassiana PfBb combined with beta cypermethrin at 10% of recommended concentration could increase the efficiency of this insecticide.